PENDAMPINGAN PENINGKATAN KUALITAS EVALUASI PEMBELAJARAN DALAM MENGANALISIS BUTIR SOAL GURU PENJASKES SE KECAMATAN RENGAT BARAT - Zulrafli Zulrafli; Kamarudin Kamarudin; Jamilin Tinambunan (Gapenas Publisher, 2023)
Community Service conducted on Penjas teachers in Rengat Barat sub-district is a partner in community service, aims to increase teacher competence and be able to prepare a good test instrument after analyzing the level of difficulty ,differentiating power of the problem, and the functioning of the distractor or Spieler problem and make the results of the analysis will make the selected set of questions and become a question bank that is ready to be tested on students when needed in the evaluation process. From the results of service activities by mentoring partner teachers, in general, have a positive impact and partner teachers in the group of Penjas teachers in West Rengat District are able to analyze the questions, hopefully in the future they can set a good instrument after the analysis and get a good quality evaluation